Intraoperative Intracerebral MRI-Guided Navigation for Accurate Targeting in Nonhuman Primates - Marina E. Emborg M.D., Ph.D.; Valerie Joers; Ronald Fisher; Kevin Brunner; Victoria Carter; Chris Ross; Raghu Raghavan; Martin Brady; James Raschke; Ken Kubota; Andrew Alexander (Cell Transplantation, 2010)
During in vivo intracerebral infusions, the ability to perform accurate targeting towards a 3D-specific point allows control of the anatomical variable and identification of the effects of variations in other factors. Intraoperative MRI navigation systems are currently being used in the clinic, yet their use in nonhuman primates and MRI monitoring of intracerebral infusions has not been reported. In this study rhesus monkeys were placed in a MRI-compatible stereotaxic frame. T1 MRIs in the three planes were obtained in a 3.0T GE scanner to identify the target and plan the trajectory to ventral postcommisural putamen. A craniotomy was performed under sterile surgical conditions at the trajectory entry point. A modified MRI-compatible trajectory guide base (Medtronic Inc.) was secured above the cranial opening and the alignment stem applied. Scans were taken to define the position of the alignment stem. When the projection of the catheter in the three planes matched the desired trajectory to the target, the base was locked in position. A catheter replaced the alignment stem and was slowly introduced to the final target structure. Additional scans were performed to confirm trajectory and during the infusion of a solution of gadoteridol (ProHance, Bracco Diagnostics; 2 mM/L) and bromophenol blue (0.16 mg/ml) in saline. Monitoring of the pressure in the infusion lines was performed using pressure monitoring and infusion pump controller system (Engineering Resources Group Inc.) in combination with a MRI-compatible infusion pump (Harvard). MRI during infusion confirmed successful targeting and matched postmortem visualization of bromophenol blue. Assessment of the accuracy of the targeting revealed an overall 3D mean ± SD distance error of 1.2 ± 0.6 mm and angular distance error of 0.9 ± 0.5 mm. Our results in nonhuman primates confirm the accuracy of intraoperative MRI intracerebral navigation combined with an adaptable, pivot point-based targeting system and validates its use for preclinical intracerebral procedures.